Creative Writing as Freedom, Education as Exploration - Nicole Anae (Australian Journal of Teacher Education, 2023)
The themed presentation at the Sydney Writers’ Festival on May 25, 2013 entitled “Creative Writing as Freedom, Education as Exploration” brought together three key players in a discussion about imaginative freedom, and the evidence suggesting that the impact of creativity and creative writing on young minds held long lasting, ongoing implications. This is a particularly crucial conversation given the factors stifling creative writing pedagogies in contemporary classrooms. In contributing to the ongoing dialogue about literary creativity, this theorized classroom-based discussion explores the integration of creative writing as literary and visual arts pedagogy among first year preservice-teachers developing an autoethnographic project. By modifying traditional autoethnographic methodology to include literary and Arts-based approaches to creative writing, the examination argues that, while “Creative writing is more than just words on a page; it’s freedom”, developing confidence and competencies among first year teacher-education students may prove important to the educational futurity of that philosophy